Teach yourself visually more jewelry making : techniques to take your projects to the next level - Michaels, Chris Franchetti. (Teach yourself visually, 2012)
Beginning with a concise overview of jewelry making tools and essential techniques, the book gives you technique-specific chapters covering: basic metal work, metal cold connections, sculpting with metal clay, embellishing metal, designing with chain, using adhesives, and working with art glaze, resin, and leather. Plus, a final chapter devoted to example projects gives you instruction for making 12 unique pieces to add to your jewelry collection.